2006
DOI: 10.1111/j.1365-2214.2006.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Costs of caring for a child with cancer: a questionnaire survey

Abstract: Although families are offered timely information about their entitlement to benefits, financial problems are incurred by families of a child with cancer partly because legislation prevents benefits being claimed for the first 3 months of a child's illness - the time when expenses are still at their highest. Furthermore, because benefits are backdated only to the point at which the claim was made, families do not recoup all their costs. Waiving of the 84-day wait period for children undergoing chemotherapy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(143 citation statements)
references
References 10 publications
4
135
4
Order By: Relevance
“…The non-significant gender differences in this study are of interest since previous studies with shorter follow-up periods have reported differences between mothers and fathers [6][7][8]. With a long-term perspective applied, no such differences were observed.…”
Section: Interpretation Of Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…The non-significant gender differences in this study are of interest since previous studies with shorter follow-up periods have reported differences between mothers and fathers [6][7][8]. With a long-term perspective applied, no such differences were observed.…”
Section: Interpretation Of Resultsmentioning
confidence: 49%
“…A substantial number of parents of children diagnosed with cancer experience significant occupational and financial consequences including employment and income loss, affected work ability, reduced work hours, and sick leave, both during and after treatment completion [3,4]. The impact on parental income, employment and sick leave is greatest during treatment and the effect on employment and earnings is greater among mothers than fathers [3,[5][6][7][8]. There is a lack of longitudinal studies with long-term follow-up on the impact of childhood cancer on parents' work situation.…”
Section: Original Articlementioning
confidence: 99%
“…1 Financial concerns have been identified as a major stressor for families of children receiving cancer treatment across a wide range of health systems, benefit models, and economic climates. [2][3][4][5][6] The financial burden on families whose children die has been less well elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…can have their access to this tertiary health service facilitated whereas those coming from intermediate and far cities face difficulty accessing care and not return to the service with the ideal frequency due to the distance (6) and financial difficulties (19) , which may interfere on the …”
Section: Discussionmentioning
confidence: 99%